Early Prognostic Evaluation of Acute Pancreatitis: An On-Going Challenge - Kapoor, Karan; Banks, Peter A (JOP. Journal of the Pancreas, 2013)
No abstract available. Image: Logo (University of Medicine and Dentistry of New Jersey - UMDNJ. Newark, NJ, USA).